Profile of an occupation – railway worker specialising in operational train driving and transport - Schambeck, Arne [Verfasser] (My University, 2022)
"Train drivers steer trains and transport freight or passengers locally or across long distances. They have a major part to play in the implementation of a climate-friendly transport policy. As a consequence, the need for qualified skilled workers is high. This occupational description provides information on the new training regulations, presents figures relating to the proportion of women in the job and states digitalisation trends." (author's abstract; BIBB-Doku)
Keywords: S 6.4.2.1 Verkehrsberufe (inkl. Nachrichtenverkehr); 370; Eisenbahner im Betriebsdienst; Verkehrsberuf; Neuordnung der Ausbildungsberufe